2010
DOI: 10.1007/s11427-010-4013-5
|View full text |Cite
|
Sign up to set email alerts
|

Canopy and leaf gas exchange of Haloxylon ammodendron under different soil moisture regimes

Abstract: In order to reveal the drought resistance and adaptation of the C(4) desert plant Haloxylon ammodendron under artificially controlled soil moisture regimes, representative plants were selected to measure canopy photosynthesis using canopy photosynthetic measurement system. The results showed that appropriate soil moisture significantly enhances the canopy and leaf photosynthetic capacity, and extremely high soil moisture is not conducive to the photosynthesis of H. ammodendron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…A reasonable irrigation amount and mulch can reduce the activity of nitrate reductase, increase the chlorophyll content of leaves, accumulate carbohydrates of vascular bundle sheath cells, and enhance the gas exchange capacity of maize leaves, and finally improve the photosynthetic carbonization ability of maize. Previous studies have found that too much or too little water is not conducive to photosynthesis [24]. Appropriate irrigation and biodegradable film coverage keep the soil moisture at an appropriate level, which is conducive to photosynthesis.…”
Section: Effect Of Irrigation Amount On G S and C I Of Degradable Filmentioning
confidence: 99%
“…A reasonable irrigation amount and mulch can reduce the activity of nitrate reductase, increase the chlorophyll content of leaves, accumulate carbohydrates of vascular bundle sheath cells, and enhance the gas exchange capacity of maize leaves, and finally improve the photosynthetic carbonization ability of maize. Previous studies have found that too much or too little water is not conducive to photosynthesis [24]. Appropriate irrigation and biodegradable film coverage keep the soil moisture at an appropriate level, which is conducive to photosynthesis.…”
Section: Effect Of Irrigation Amount On G S and C I Of Degradable Filmentioning
confidence: 99%
“…Since the mean stomatal resistance of single leaves cannot be measured directly due to the diversity of the vegetation, a value of 200 s/m was adopted for the oasis-desert transition zone based on prior works (Stannard, 1993;Allen et al, 1998;Liu and Zhao, 2009;Gao et al, 2010). Figure 2 shows some of the meteorological data of the study area.…”
Section: Penman-monteith Model (Et C )mentioning
confidence: 99%
“…In Haloxylon ammodendron, a typical desert plant of the middle reach of the inland Heihe River Basin, the leaf and canopy photosynthetic rates and the photosynthetic capacity will peak when soil moisture content is maintained at (50 � 10)% of field capacity. If soil moisture increases or decreases, the photosynthetic capacity of H. ammodendron declines (Gao et al 2010). Meanwhile, based on the current field investigation and previous experiments, most desert species suffered severe water stress when soil moisture content was maintained at approximately 20% of field capacity.…”
Section: Experimental Design and Plant Speciesmentioning
confidence: 70%
“…Usually, the transpiration rate does not decrease significantly until the soil moisture falls below 50% of field capacity (Soundar, Vijayalakshmi, and Mariappan 2010). Figure 2 shows that the T under the FC 50% treatment in the middle reach was significantly higher than that under FC 20% in the same region and under these two water regimes in the lower reach; H. ammodendron in the middle reach had a strong ability to assimilate carbon (Gao et al 2010). FC 50% was considered to be a moderate moisture condition for desert plants in the middle reach, because no significant difference was observed in the need for water and water consumption of different plants (Figure 3).…”
Section: Discussionmentioning
confidence: 97%